Respuesta :
Answer:
58
Step-by-step explanation:
a = 27, b = -10 and c = 40
= a - (6 - c) + (a - b) - C
= 27 - (6 - 40) + (27 - (-10)) - 40
= 27 - (-34) + (37) - 40
= 27 + 34 + 37 - 40
= 58
[tex]\huge\textsf{Hey there!}[/tex]
[tex]\large\textsf{a - (6 - c) + (a - b) - c}[/tex]
[tex]\large\textsf{= 27 - (6 - 40) + (27 - (-10)) - 40}[/tex]
[tex]\large\textsf{6 - 40 = \bf -34}[/tex]
[tex]\large\textsf{= 27 - (-34) + (27 - (-10)) - 40}[/tex]
[tex]\large\textsf{= 27 + 34 + 27 + 10 - 40}[/tex]
[tex]\large\textsf{27 + 34 = \bf 61}[/tex]
[tex]\large\textsf{= 61 + 27 + 10 - 40}[/tex]
[tex]\large\textsf{61 + 27 = \bf 88}[/tex]
[tex]\large\textsf{88 + 10 - 40}[/tex]
[tex]\large\textsf{88 + 10 = \bf 98}[/tex]
[tex]\large\textsf{98 - 40}[/tex]
[tex]\large\textsf{= \bf 58}[/tex]
[tex]\boxed{\boxed{\large\textsf{Answer: \huge \bf 58}}}\huge\checkmark[/tex]
[tex]\large\textsf{Good luck on your assignment and enjoy your day!}[/tex]
~[tex]\frak{Amphitrite1040:)}[/tex]